Diagnosis of left ventricular noncompaction by computed tomography - Benjamin, Mina M. (Baylor Health Care System, 2012)
Left ventricular noncompaction (LVNC) is a rare disorder in which the left ventricular endocardial surface is not appropriately flattened and is heavily trabeculated. Patients with this condition can be affected by stroke from emboli that originate from these recesses. We present a patient with LVNC who was originally misdiagnosed as having an idiopathic dilated cardiomyopathy. Ultimately, diagnosis of LVNC was confirmed through the use of 64-slice multidetector cardiac computed tomography (CT). There are few reports of using multidetector CT for diagnosis of LVNC, but this appears to be a viable option in confirming the diagnosis and at the same time assessing the coronary arteries. The recognition of this cardiomyopathy and its differentiation from other nonischemic cardiomyopathies have important implications for the patient and for family members, given its potential familial inheritance patterns and poor long-term prognosis.